The Local Food Crisis in Iraq Between Thoughts of the Malthusian Theory and the Agricultural Section Regression Reality - ناشور الهام خزعل (Journal of Economics and Administrative Sciences, 2016)
Most countries in the world particularly developing countries, including Iraq, facing extremely dangerous problem with social and political dimensions, which is the emergence of the food crisis problem ,the decrease in domestic food production in Iraq isn’t meet the needs of its population food, due to the fact that the agricultural sector suffers from multiple natural ,economic and human problems .It is still below the level required to meet the needs of the population of food ,since food at the forefront of priorities needed by the human . This represents indispensable basic necessity , so the responsibility of its availability permanently in appropriate quantity and type should be done by the state and its related institutions because it is a human right ,for this the presence of food crisis in Iraq and their increase is a big dilemma should be addressed through the availability of the necessary quantities of food for the local population and improve the quality of food affordable that they have. But we find that the state instead of take strategic solutions to face the crisis worked to increase agricultural production tended to containment of crisis by imports from abroad, this is what will put the state in large risks that are difficult to face in the future ,and due to the importance of that issue, the study reveal the reality of the food crisis in Iraq, and the reasons leading to it, so that to find ways to address them.